Hak-Hak Tersangka Dalam Proses Penyidikan Perspektif Hukum Pidana Islam - Nasution, Gilang Real Juhandra; Ishaq, Ishaq (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
The rights of suspects are very important in the criminal justice system. This research aims to examine the rights of suspects in the investigation process according to the perspective of Islamic criminal law. This research uses two problem formulations, namely what are the suspect's rights in the investigation process from a positive criminal law perspective in Indonesia and what are the suspect's rights in the investigation process from an Islamic criminal law perspective. The research is qualitative research with a normative juridical type of research, using primary data sources. The results of this research show that suspects' rights include the presumption of innocence, legal defense, and decent treatment. Another important thing is the right to receive an investigation process that is in accordance with legal procedures and complies with human rights principles. The rights of suspects in the investigation process according to positive law in Indonesia are in line with Islamic criminal law